2016
DOI: 10.1021/acs.inorgchem.6b00968
|View full text |Cite
|
Sign up to set email alerts
|

Topological Study of Bonding in Aquo and Bis(triazinyl)pyridine Complexes of Trivalent Lanthanides and Actinides: Does Covalency Imply Stability?

Abstract: The geometrical and electronic structures of Ln[(HO)] and [Ln(BTP)], where Ln = Ce-Lu, have been evaluated at the density functional level of theory using three related exchange-correlation (xc-)functionals. The BHLYP xc-functional was found to be most accurate, and this, along with the B3LYP functional, was used as the basis for topological studies of the electron density via the quantum theory of atoms in molecules (QTAIM). This analysis revealed that, for both sets of complexes, bonding was almost identical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 81 publications
4
54
0
Order By: Relevance
“…Fryer-Kanssen et al have investigated the relationship between metal-ligand bond covalency and complex stability in [M(BTP) 3 ] 3+ complexes with M = Ln, Am, Cm. 57 and, in agreement with previous energetic studies, [74][75][76][77][78] found evidence for the relative stability of [An(BTP) 3 ] 3+ over the Ln analogues. While An covalency was found to be higher in both the aquo and BTP complexes, the relative increase was larger in the latter, providing indirect evidence for covalent bond stabilisation in the An complex.…”
Section: Correlating Covalency With Bond Strengthsupporting
confidence: 89%
See 1 more Smart Citation
“…Fryer-Kanssen et al have investigated the relationship between metal-ligand bond covalency and complex stability in [M(BTP) 3 ] 3+ complexes with M = Ln, Am, Cm. 57 and, in agreement with previous energetic studies, [74][75][76][77][78] found evidence for the relative stability of [An(BTP) 3 ] 3+ over the Ln analogues. While An covalency was found to be higher in both the aquo and BTP complexes, the relative increase was larger in the latter, providing indirect evidence for covalent bond stabilisation in the An complex.…”
Section: Correlating Covalency With Bond Strengthsupporting
confidence: 89%
“…The only systematic study in the literature is that of Fryer-Kanssen et al, who investigated [Ln(H 2 O) 9 ] 3+ and [Ln(BTP) 3 ] 3+ (BTP = bis(triazinyl)pyridine) complexes with Ln = Ce-Lu. 57 As might be expected, topological analysis of densities generated using the hybrid-GGA exchange-correlation functionals B3LYP and BHLYP revealed low values of r BCP in all cases and only small (o10%) variation as the series was traversed, indicative of predominantly ionic bonding with little dependence on the nature of the central ion, see Fig. 4.…”
Section: View Article Onlinesupporting
confidence: 69%
“…The metrics employed herein have been used extensively to characterize bonding in situ and have been shown to be particularly useful in f element chemistry. 4,31,[36][37][38][39] Data for the bond critical point (BCP) metrics (electron density, ρBCP, its Laplacian ∇ 2 ρBCP, and the total energy density HBCP) and integrated QTAIM properties (atomic charge, q, and the delocalization index of the M and O atom pair, δ(M,O)) are shown in Table 2 for the optimized M(OC6H5)4 systems (and for the systems at r(M-O) -0.12 Å in Table SI2 of the Supplementary Information). The magnitudes of ρBCP and HBCP are measures of covalency, where values of ρBCP > 0.2 au and HBCP < 0 indicate interactions with significant sharing of electrons, or covalent character.…”
Section: Quantum Theory Of Atoms In Molecules Analysismentioning
confidence: 99%
“…Part of (M) is manifested in the DI(M,N) delocalization indices (Table 3) in which the integrated parameter has helped in the elucidation of weak trends in the bonding of various lanthanide-and actinide-containing molecules [28,[52][53][54][55][56][57][58][59][60]. DI quantifies the average number of electrons shared between two atoms connected by a bond path [52].…”
Section: R(iii) Bmentioning
confidence: 99%
“…As one of the main results, we found increasing metal-ligand interactions along the Ln series. A recent topological study of [Ln(BTP) 3 ] 3+ derivatives, by Fryer-Kanssen et al [28], reported low charge densities at the Ln-N bond critical points (BCPs) and very small irregular variation as the series was traversed. Comparison of the integrated properties of the Eu and Gd complexes with those of Am and Cm indicated slightly larger metal-ligand covalent bonding contributions in the actinide complexes.…”
Section: Introductionmentioning
confidence: 99%